The role of cryptochrome 1a in long-distance signaling of water deficit in tomato - Damião, Victor D’Amico [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
It is well known that light is a crucial environmental factor that has a fundamental role in plant growth and development from seed germination to fruiting. For this process, plants contain versatile and multifaceted photoreceptor systems to sense variations in the light spectrum and to acclimate to a range of ambient conditions. Five main groups of photoreceptors have been found in higher plants, cryptochromes, phototropins, UVR8, zeitlupes and phytochromes, but the last one red/far red wavelengths photoreceptor is the most characterized. Among the many responses modulated by phytochromes, these molecules play an important role in biotic and abiotic stress responses, which is one of the most active research topics in plant biology, especially their effect on agronomic traits. However, regarding the light spectrum, it is not surprising to consider that other photoreceptors are also part of the stress response modulated by light. In fact, it has become increasingly evident that cryptochromes, which mainly absorb in the blue light region, also act as key regulators of a range of plant stress responses, such as drought, salinity, heat and high radiation. However, this information is rarely evidenced in photomorphogenetic studies. Therefore, the scope of the charpter 1 is (i) to compile and discuss the evidence on the abiotic stress responses in plants that are modulated by cryptochromes. In addition, chapters 2, 3 and 4 refer to the respective manuscripts: (ii) physiological characterization of the tomato cry1a mutant; (iii) characterization of tomato cry1a mutant seedlings under osmotic stress and different rates of blue light fluencies; and (iv) the study of plant water stress responses using the photomorphogenetic mutant cry1a and grafting to understand the role of this photoreceptor in long-distance signaling.

É bem conhecido que a luz é um fator ambiental crucial que tem papel fundamental no crescimento ne desenvolvimento das plantas, desde a germinação das sementes até a frutificação. Para este processo, as plantas contêm sistemas fotorreceptores versáteis e multifacetados para detectar variações no espectro de luz e se aclimatar a uma variedade de condições ambientais. Cinco grupos principais de fotorreceptores foram encontrados em plantas superiores, criptocromos, fototropinas, UVR8, zeitlupes e fitocromos, mas o último fotorreceptor de comprimento de onda vermelho/vermelho distante é o mais caracterizado. Dentre as muitas respostas moduladas por fitocromos, essas moléculas desempenham um papel importante nas respostas ao estresse biótico e abiótico, que é um dos tópicos de pesquisa mais ativos em biologia vegetal, especialmente seu efeito sobre características agronômicas. Porém, em relação ao espectro de luz, não é surpreendente considerar que outros fotorreceptores também fazem parte da resposta ao estresse modulada pela luz. Na verdade, tornou-se cada vez mais evidente que os criptocromos, que absorvem principalmente na região da luz azul, também atuam como reguladores principais de uma série de respostas ao estresse das plantas, como seca, salinidade, calor e alta radiação. No entanto, essa informação raramente é evidenciada em estudos fotomorfogenéticos. Portanto, o escopo do capítulo 1 é (i) compilar e discutir as evidências sobre as respostas ao estresse abiótico em plantas que são moduladas por criptocromos. Além disso, os capítulos 2, 3 e 4 referem-se aos respectivos manuscritos: (ii) caracterização fisiológica do mutante cry1a de tomateiro; (iii) caracterização de plântulas do mutante cry1a de tomateiro sob estresse osmótico e diferentes taxas de fluências de luz azul; e (iv) o estudo das respostas ao estresse hídrico das plantas utilizando o mutante fotomorfogenético cry1a e enxertia para entender o papel deste fotorreceptor na sinalização de longa distância.
O papel do criptocromo 1a na sinalização de longa distância do déficit hídrico em tomateiro
Keywords: Blue-light fluence; Cryptochrome 1a; Osmotic stress; Root-shoot signaling; Solanum lycopersicum L.; Water deficit